Unlocking the potential of teff for sustainable, gluten-free diets and unravelling its production challenges to address global food and nutrition security: a review - Adepoju, Mary; Verheecke-Vaessen, Carol; Pillai, Laxmi Ravikumar; Phillips, Heidi; Cervini, Carla (MDPI, 2024)
Sustainable diets, as defined by the Food and Agriculture Organisation, aim to be nutritionally adequate, safe, and healthy, while optimising natural and human resources. Teff (Eragrostis tef), a gluten-free grain primarily grown in Ethiopia, has emerged as a key contender in this context. Widely regarded as a “supergrain”, teff offers an outstanding nutrition profile, making it an excellent choice for people with gluten-related disorders. Rich with protein, essential amino acids, polyunsaturated fats, and fibre, and abundant in minerals like calcium and iron, teff rivals other popular grains like quinoa and durum wheat in promoting human health. Beyond its nutritional benefits, teff is a hardy crop that thrives in diverse climates, tolerating both drought and waterlogged conditions. Due to its resilience and rich nutrient content, teff holds the potential to address nine of the 17 United Nations’ Sustainable Development Goals (SDGs), including SDG 1 (no poverty), SDG 2 (zero hunger), and SDG 3 (good health and wellbeing), which are tied to improving food and nutrition security. However, teff production in Ethiopia faces significant issues. Traditional farming practices, insufficient storage infrastructure, and food safety challenges, including adulteration, hinder teff’s full potential. This review explores teff’s dual role as a nutritious, sustainable food source and outlines the key challenges in its production to conclude on what needs to be done for its adoption as a golden crop to address global food and nutrition security.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 3006 Food Sciences; Nutrition; 3.3 Nutrition and chemoprevention; Generic health relevance; 2 Zero Hunger; 3106 Industrial biotechnology; teff; gluten free; sustainable diet